Finance Theory - Dothan, Michael U. (Review of Financial Studies, 1988)
The author presents a self-contained exposition of selected topics in the theory of financial markets with applications to corporate finance. The book covers only topics sanctioned by tradition. About one-quarter of the book is devoted to the one-period model with certainty. Half the book deals with the one-period model with uncertainty, and the remaining quarter with multiperiod models with uncertainty, both discrete and continuous. The one-period model with certainty starts with topics from the standard theory of the consumer and discusses consumer preferences and their representation by utility functions. The author then defines arbitrage trading strategies and uses the assumed properties of preferences to show that equilibrium in this model excludes arbitrage trading strategies. In the absence of arbitrage trading strategies all securities earn the same rate of return. The price functional, which maps terminal cash flows into initial prices, is additive, and the irrelevance of corporate financial structure and dividend policy follows from the additivity of the price functional.